Pengaruh Penyuluhan Gizi Seimbang terhadap Tingkat Pengetahuan dan Sikap pada Remaja Putri di MAS Al-Muhajirin Pandan - Ngaisah Tri Rahayu; Khairulisni Saniati; Asri Fitri Yati; Hearty Efifania Ose Payon (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
In 2020, Indonesia faced several problems such as stunting, wasting, obesity, and micronutrient deficiencies such as anemia. Adolescents are an age group at risk of both malnutrition and overnutrition. Nutritional problems in adolescents are often caused by several factors such as unhealthy eating habits, incorrect understanding of nutrition, and a tendency to overindulge in one type of food. The purpose of this study was to determine the effect of balanced nutrition counseling on the knowledge and attitudes of adolescent girls. The research method used quantitative with a pre-experimental method. This study was conducted at MAS Al-Muhajirin Pandan in May 2025. The population in this study were all adolescent girls at MAS Al-Muhajirin Pandan totaling 60 respondents. The sample in this study used total sampling. Data analysis used the T-Test. The results of the study showed that there was an effect of balanced nutrition counseling on the level of knowledge with a p-value of 0.039 and there was an effect of balanced nutrition counseling on adolescent attitudes with a p-value of 0.015.